2021
DOI: 10.3390/polym13101657
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Corrosion Resistance of Graphene Oxide-Based Epoxy Zinc-Rich Coatings

Abstract: In order to improve the corrosion resistance of zinc-rich epoxy coatings and reduce the amount of zinc used, first, graphene oxide (GO) was modified by sulfonated multiwall carbon nanotubes (SMWCNTs) to obtain the modified graphene oxide (SM-GO). The samples were characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and Raman spectroscopy. Then, four kinds of coatings were prepared, namely pure zinc-rich coating (0-ZRC), graphene oxide-based zinc-rich coating (GO-ZRC), sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…The exponents CPEd-P reveal the high non-homogeneity of surface in all samples. The experimental show the similar behaviour with those reported in the literature [24,27,[30][31][32][33][34][46][47][48]. The G coatings investigated in this work show a higher Rct values comparatively with graphene oxide PU coatings reported by Wang and co also for Al [36].…”
Section: Electrochemical Testssupporting
confidence: 89%
See 1 more Smart Citation
“…The exponents CPEd-P reveal the high non-homogeneity of surface in all samples. The experimental show the similar behaviour with those reported in the literature [24,27,[30][31][32][33][34][46][47][48]. The G coatings investigated in this work show a higher Rct values comparatively with graphene oxide PU coatings reported by Wang and co also for Al [36].…”
Section: Electrochemical Testssupporting
confidence: 89%
“…For example, sulfonated multiwall carbon nanotubes (SMWCNTs) are used to non-covalently modify graphene oxide (GO) to obtain modified graphene oxide (SM-GO) [ 30 ] or functionalisation of silica nanoparticle to obtain the SiO2-GO nanostructure [ 31 ], which led to the improvement of the dispersion in the coating matrix, as well as the mechanical and thermal properties of epoxy nanocomposites. In the case of PU coatings, by adding 0.1 wt.% of GO and polyisocyanate (PI) resin grafted onto the GO surface (PI-GO) nanosheets, an improvement in the corrosion protection properties was obtained [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to confirm the presence of graphene oxide on the surface of austenitic steel 1.4541, FTIR studies were performed which showed a positive result when applying GO on the surface (BM + GO). Figure 5 shows typical absorption bands characteristic for oxidized domains of GO [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to confirm the presence of graphene oxide on the surface of austenitic steel 1.4541, FTIR studies were performed which showed a positive result when applying GO on the surface (BM + GO). Figure 5 shows typical absorption bands characteristic for oxidized domains of GO [16]. The GO samples (BM + GO) have absorption peaks at 3289 cm −1 , 2976 cm −1 , 1745 cm −1 , 1636 cm −1 , 1238 cm −1 , and 1156 cm −1 corresponding to the vibrations of the C-O bond, C=C bond, C=O bond, aliphatic C-H, and O-H bond, respectively.…”
Section: Surface Morphologymentioning
confidence: 99%
“…Bringing conductive or low electrical resistance properties to sol-gel anticorrosive and UV-curable coatings has been attempted by dispersing conductive nanofillers within the solgel matrices. Unfortunately, it was shown that this incorporation cause a negative effect on the achieved anticorrosive properties since the fillers compromise the mechanical and barrier properties of the coatings creating local defects and provide an electrical path for corrosion to take place (Zhang Q. et al, 2018;Agustín-Sáenz et al, 2020;Tian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%